Medication treatment of singultus in palliative care - Kováčová, Barbora (Casopis lekaru ceskych, 2019)
Singultus (hiccup) is caused by periodic involuntary spastic contractions of the respiratory muscles followed by a sharp inspiration and early glottis closure. This results in typical "hic" sound. Brief episodes of hiccups are quite common experience in general population, and they do not indicate serious disease nor require medical treatment. If chronic, they pose a significant problem with plethora of negative consequences on patient condition, particularly in palliative care. Treatment options involve many approaches - both nonmedication and medication options. However, there are no large controlled trials resulting in unambiguous recommendations. Current pharmacologic treatment strategies are therefore only based on small studies and case reports and they report more or less successful outcomes using medications with different mechanisms of action.
Keywords: paliativní péče; pharmacotherapy; cancer patient; Hiccup; Humans; škytavka; lidé; palliative care; singultus; Palliative Care